Effects of exercise on bone mass and bone metabolism in adolescents: a systematic review and meta-analysis - Zhang, Wenhua; Wang, Xiaoqiang; Liu, Yurong; He, Qiang; Ding, Qixin; Mei, Jingqi; Li, Xun (Frontiers in Physiology, 2024)
ObjectiveMeta-analysis was used to evaluate the effects of an exercise intervention on bone mineral content (BMC), bone mineral density (BMD), and bone metabolism in adolescents.MethodsA systematic search of PubMed, Embase, Cochrane Library, and Web of Science for RCTs on “exercise, adolescents, BMD, bone metabolism” up to 10 September 2024. Included RCTs focused on effects of exercise on BMC, BMD, and bone metabolism in 10–19 years old, with physical activity as exercise group and daily living/primal exercise as control group. Outcome metrics included lumbar spine, femoral neck, whole body BMC and BMD, bone alkaline phosphatase (BALP), procollagen type 1N-terminal propeptide (PINP), osteocalcin (OC), and type I collagen carboxy-terminal peptide (CTX). Exclusion criteria included duplicates, non-RCTs, non-adolescent studies, and non-compliance with indicators. Meta-analyses were performed using RevMan 5.4, and quality assessed by Cochrane’s tool. Effect sizes were estimated using standardized mean differences (SMDs) and 95% confidence intervals (CIs), and heterogeneity was assessed using the I2 statistic to determine fixed or random effects models.ResultsFifteen articles with a total of 723 subjects were included. The meta-analysis showed that, compared to the control group, (i) exercise was effective in increasing adolescents’ overall BMC (SMD = 0.16, 95% CI: 0.06–0.27, p = 0.003) and BMD (SMD = 0.26, 95% CI: 0.13–0.40, p = 0.0001). (ii) Subgroup analyses showed that exercise significantly increased adolescents’ lumbar spine BMC (SMD = 0.17, 95% CI: 0.01–0.34, p = 0.04), femoral neck BMC (SMD = 0.23, 95% CI: 0.05–0.42, p = 0.01), lumbar spine BMD (SMD = 0.34, 95% CI: 0.12–0.56, p = 0.003) and femoral neck BMD (SMD = 0.31, 95% CI: 0.09–0.53, p = 0.007), whereas there was no statistically significant effect on whole body BMC and BMD (p > 0.05). (iii) Exercise increased BALP, and decreased PINP, OC and CTX in adolescents. but none of the differences between the exercise groups and the control group were significant (p > 0.05).ConclusionExercise is effective in improving overall BMC and BMD in adolescents and elevating BMC and BMD of the lumbar spine and femoral neck. Due to the limitation of the number and quality of the included studies, the above conclusions are yet to be validated by more high-quality empirical studies.Systematic Review Registrationhttps://www.crd.york.ac.uk/, identifier CRD42024593399